(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article is devoted to the analysis of modern credit scoring techniques, assessment of their effectiveness and identification of existing problems and risks. Various approaches to assessing borrowers’ creditworthiness are considered, including parametric and behavioral scoring, as well as the use of machine learning methods. Recommendations are offered to improve the credit scoring process, aimed at increasing its accuracy, transparency and objectivity.